Factors Influencing Face Mask Selection: Results from Pilot Study of Malaysian Umrah Pilgrims - Shahrul Anuwar, Mohamed Yusof; Imran, Abdullah; Javeed Shaikh, Mohammed (2016)
Hajj is the largest annual gathering of Muslims during which time over two million people from different parts of the world are gathered in a small area. Therefore, the risk of acute respiratory infections (ARI} 'is very high for the Hajj pilgrims. For that reason, preventive measures and control should be enhanced including the implementation of non-pharmaceutical methods of prevention such as the use of face masks, hand hygiene, respiratory etiquette, social distancing and quarantine. A pilot study was conducted in order to identify the types of face masks currently being used by Malaysian Hajj pilgrims as well as to identify the problems pertaining to the face masks being used, and to understand the factors influencing the selection of face masks by Malaysian Hajj pilgrims. Observations and survey methods were used in the pilot study. Data was collected from thirty respondents through a survey. This paper presents the results from the pilot study. Based on the factors influencing face mask selection from the pilot study, new face mask design(s) will be proposed for the Malaysian. Hajj pilgrims. It is anticipated that the use of new face mask design(s) can reduce the risk of acute respiratory infections in Malaysian Hajj pilgrims.